KAJIAN POTENSI MITOS PESUGIHAN SEBAGAI DAYA TARIK WISATA DI PESAREAN GUNUNG KAWI KABUPATEN MALANG - Pahar, Benedicta (JURNAL KEPARIWISATAAN, 2025)
Myths are part of folklore that become the cultural identity of a community that is passed down from generation to generation and has sacred value for its adherents. One of the myths that has been passed down from generation to generation is the myth of pesugihan (Indonesian term that refers to the practice of gaining supernatural wealth often by making a pact with supernatural entities) at Gunung Kawi, which still survives today. Pesarean Gunung Kawi is one of the pilgrimage tours and spiritual tours located in Malang Regency. This pesugihan myth arises because of the belief that someone will become rich after performing rituals at Pesarean Gunung Kawi. Of course, the myth of pesugihan is an unfavorable image for this tourist destination which causes someone to hesitate to visit this destination. The purpose of this research is to find out the potential of this pesugihan myth to become a unique tourist attraction and identify tourism products that can be developed in this destination by utilizing the pesugihan myth. This research uses descriptive qualitative methods with data collection techniques using interviews, observation and documentation